The impact of implementation of the requirements of Standard No. OHSAS 18001:2007 to reduce the number of injuries at work and financial costs in the Republic of Croatia. Issue 2 (3rd April 2017) - Palačić, Darko
Abstract : This article contains the results of research into the impact of implementation of the requirements mentioned in Standard No. OHSAS 18001:2007 to reduce the number of injuries at work and the financial costs incurred in this way. The study was conducted on a determined sample by a written questionnaire survey method in the Republic of Croatia. The objective of the empirical research is to determine the impact of implementation of the requirements of Standard No. OHSAS 18001:2007 to reduce the number of injuries at work and financial costs in Croatia in business organizations that implement these requirements. To provide a broader picture, the research included the collection and analysis of data on the impact of the Standard No. OHSAS 18001:2007 on accidents and fatalities at work. Research findings are based on the analysis of performed statistical data where correlation and regression analysis has been applied.